Replicating stimulus‐presentation orders in discrimination training. Issue 2 (18th November 2020) - Bergmann, Samantha; Turner, Maria; Kodak, Tiffany; Grow, Laura L.; Meyerhofer, Courtney; Niland, Haven S.; Edmonds, Kaitlyn
Abstract : Children with autism spectrum disorder (ASD) are taught conditional discriminations often during early intervention. Auditory–visual conditional discrimination (AVCD) training requires the presentation of multiple antecedent stimuli, and the order of stimulus presentation varies in the literature. This series of studies replicated previous literature on stimulus‐presentation order in AVCD training. In Experiment 1, we compared sample‐first and comparisons‐first arrangements in 8 comparisons with 4 participants with ASD. For 3 participants, both presentations were efficacious. For 1 participant, the sample‐first order was more likely to be efficacious. In Experiment 2, we added a sample‐first‐with‐repetition arrangement and conducted 6 comparisons with 5 participants with ASD. Across comparisons, all 3 presentations were efficacious. Considerations for teaching AVCD to children with ASD and suggestions for further evaluation and examination of efficacy and efficiency are discussed.